Psychiatric comorbidities in a comparative effectiveness smoking cessation trial: Relations with cessation success, treatment response, and relapse risk factors. (1st February 2020) - Johnson, Adrienne L.; Kaye, Jesse; Baker, Timothy B.; Fiore, Michael C.; Cook, Jessica W.; Piper, Megan E.
Highlights: Psychiatric diagnosis was significantly related to lower likelihood of short-term cessation. Psychiatric diagnosis was not significantly related to long-term cessation likelihood. Lifetime psychiatric diagnosis was related to elevated nicotine dependence. History of psychiatric diagnosis related to increased withdrawal-related craving. Abstract: Background: Comorbid psychiatric diagnoses have been shown to predict cessation failure. The relative impact of various diagnoses on cessation and other cessation processes is rarely studied, particularly among a general population. The impact of psychiatric history among primary care patients seeking cessation services on nicotine dependence, cessation outcomes, treatment effects and adherence, and withdrawal symptoms was examined. Methods: Secondary data analysis of a multi-site comparative effectiveness smoking cessation trial was conducted. Adult smokers ( n = 1051; 52.5 % Female, 68.1 % white) completed a structured clinical interview at baseline to assess psychiatric diagnostic history (past-year and lifetime). Nicotine dependence was assessed via self-report measures at baseline. Point-prevalence abstinence was assessed at 8 weeks and 6 months post-quit. Withdrawal symptoms were assessed for one week pre- and post-quit using ecological momentary assessment. Treatment adherence was self-reported at 1, 4, 8, and 12 weeks post-quit. Results: Past-year substance use disorder, lifetime mood disorder, and > one lifetime diagnosis, were related to lower rates of short-term, but not long-term, cessation. Lifetime psychiatric diagnosis was related to elevated nicotine dependence, particularly to secondary dependence motives associated with instrumental tobacco use. History of psychiatric diagnosis was associated with increased withdrawal-related craving. There was little evidence that psychiatric diagnostic status moderated the effects of the tested pharmacotherapies on long-term abstinence. Conclusions: Psychiatric diagnoses affect risk factors that exert their effects early in the post-quit process and highlight the potential utility of examining transdiagnostic risk factors to better understand the relations between psychiatric vulnerabilities and the smoking cessation process.